Preliminary evaluation of a raceway photobioreactor for mass culture of microalgae for Peruvian scallop, Argopecten purpuratus postlarvae - Crisóstomo-Gamboa, Rafael Octavio; Pepe-Victoriano, Renzo; Huanacuni, Jordan I.; Méndez-Ancca, Sheda; Acosta-Angulo, Olger; Cruces, Edgardo (Frontiers in Marine Science, 2025)
Feeding microalgae during the larval and post-larval stages of bivalve mollusks is necessary to overcome the high mortality rates that occur during metamorphosis. Proper selection of the microalgae species and strain to be used by considering its nutritional value, cell density, culture time, and type of culture system to improve bivalve productivity is of high importance. In this study a microalgae recirculating culture system was evaluated. The system consisted of an open horizontal photobioreactor inside a hatchery raceway tank (12 m long, 2 m wide, and 0.5 m high) with a central division of 10 m and a driving paddle that generated a continuous flow of water at a speed of 1.25 m/s. The microalgae species cultivated in the photobioreactor were strains of Nannochloris spp. and Phaeodactylum spp., with the former reaching a significantly higher cell density of 19.37 ± 1.31 (106 cell mL-1) than the latter, which obtained a cell density of 1.41± 1.31 (106 cell mL-1). The reproductive cycle for Nannochloris spp. was 59 d, whereas that for Phaeodactylum spp. was 19 d. This study demonstrates that, although both strains of species of microalgae can be cultivated utilizing a horizontal photobioreactor system in hatcheries, Nannochloris spp. strains offer productive advantages including culture duration.